Evaluation of the Effect of the Parameters Involved in Generating of Digital Orthophoto on its Horizontal Accuracy - الخليل, عمر; ديوب, وائل; خيربك, ميار (Latakia University Journal -Engineering Sciences Series, 2021)
In this research, we seek to study the effect of the accuracy of the digital elevation model (DEM) interpolated by deterministic and stochastic methods, as well as the effect of the inner and outer orientation parameters on the geometric quality of the orthophoto. We also aim to test DEM and orthophoto resulting from the application of Structure from Motion (SfM) photogrammetry to see if it enables us to obtain higher accuracy and reliability than traditional methods. Finally, we discussed a practical application for selecting the best interpolation method for the digital elevation model from elevation points extracted from topographic map and then evaluating the resulting orthophoto using this model and the SfM technique. Practical experience has shown that using this technique it is possible to improve the vertical accuracy of the digital elevation model by up to twice as compared to conventional methods (vertical accuracy improved from 0.0603 m to 0.0355 m).